2017
DOI: 10.21449/ijate.370494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Comparability of PPT and CBT by Implementing the Compulsory Islamic Culture Course Test in Jordan University

Abstract: Study aims to determine whether the university students' scores in the compulsory Islamic culture course test on a selected sample differ across the paper-and pencil test (PPT) & computer-based test (CBT) versions, and to reveal the relationship between gender and the student's level of performance in the test. Therefore, the study evaluated the comparability of two versions of a compulsory Islamic culture course test (PPTs) and (CBTs). The importance of conducting the study in Jordan stems from the fact that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Many studies have been conducted on the comparability of CBT and PPT. Some of the studies (Choi et al, 2003;Scheuermann & Björnsson, 2009) revealed that there is a significant difference between the two testing modes on test scores, while other studies (Al-Amri, 2009;Alakyleh, 2018) reported opposite or inconsistent results. Alakyleh's (2018) study aims to determine whether the university students' scores in the compulsory Islamic culture course test on a selected sample differ across the paper and pencil test (PPT) & computer-based test (CBT) versions and to reveal the relationship between gender and the student's level of performance in the test.…”
Section: Figure 1 Appraisal Of Candidates' Achievement In the West Af...mentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies have been conducted on the comparability of CBT and PPT. Some of the studies (Choi et al, 2003;Scheuermann & Björnsson, 2009) revealed that there is a significant difference between the two testing modes on test scores, while other studies (Al-Amri, 2009;Alakyleh, 2018) reported opposite or inconsistent results. Alakyleh's (2018) study aims to determine whether the university students' scores in the compulsory Islamic culture course test on a selected sample differ across the paper and pencil test (PPT) & computer-based test (CBT) versions and to reveal the relationship between gender and the student's level of performance in the test.…”
Section: Figure 1 Appraisal Of Candidates' Achievement In the West Af...mentioning
confidence: 98%
“…Some of the studies (Choi et al, 2003;Scheuermann & Björnsson, 2009) revealed that there is a significant difference between the two testing modes on test scores, while other studies (Al-Amri, 2009;Alakyleh, 2018) reported opposite or inconsistent results. Alakyleh's (2018) study aims to determine whether the university students' scores in the compulsory Islamic culture course test on a selected sample differ across the paper and pencil test (PPT) & computer-based test (CBT) versions and to reveal the relationship between gender and the student's level of performance in the test. The results showed that there was no significant difference between the two versions provided to students, CBT and PPT,with .36 The Gambia Also, research findings on the preference for CBT or PPT by various stakeholders in the field of education and other fields of study have been quite varied in the literature.…”
Section: Figure 1 Appraisal Of Candidates' Achievement In the West Af...mentioning
confidence: 98%
“…In some studies, test takers outperformed on PPBT rather than CFLT (Carpenter & Alloway, 2018;Hosseini et al, 2014), or no testing administration mode effect was found (Jeong, 2012;Karay et al, 2015;Meyer et al, 2016;Prisacari & Danielson, 2017). Although these results cannot be described as decisive, there is a growing tendency to suggest that two CFLT and PPBT versions are expected to be equivalent across two presentation modes (Alakyleh, 2018;Ebrahimi et al, 2019;Khoshsima et al, 2019;Wang & Shin, 2010). Converting PPBT into CFLT and studying mode effect on testing performance should be done through carefully well-organized empirical investigations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in the age of technologizing assessment (Ary et al, 2018), teachers are capable and intelligent enough to create their own CFLT versions to assess their students' attainments, and consequently to make instructional decisions (Hensley, 2015). This is the main reason leads some researchers in middle-eastern countries such as Iran, Japan, Hong- Kong, China, Thailand, Turkey, Saudi Arabia, Malaysia, and Jordan (Hashemi Toroujeni, Thompson, and Faghihi, In Press) to investigate whether test-takers' scores are equivalent across two test versions (Alakyleh, 2018). Therefore, scores across two delivery modes or across different times need to be interchangeable or equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…This testing has many benefits. In the testing field, Alakyleh (2018) affirmed that the use of computers contributed to increased productivity and creativity. CBT facilitated test authors to contribute identical test settings for all examinees, regardless of the size of the test population.…”
Section: Introductionmentioning
confidence: 99%